Experiences of Mothers' Attachment in a Follow-Up Program Using Early Intervention for Low-Birth-Weight Infants - Jia Lee; Jinhee Choi Kang; Eun Sun Ji (Elsevier, 2019)
Summary: Purpose: Mothers who give birth prematurely experience parenting stress after their babies are discharged and find it difficult to emotionally bond with them. Forming an emotional bond with a baby promotes the baby's growth and development, helps the mother cope with parenting stress after discharge, and is important for maintaining family functioning. This study aimed to identify the attachment experiences of mothers with low-birth-weight infants (LBWIs) in a follow-up program using early intervention. Methods: A phenomenological perspective was used for this qualitative research. Data were collected from in-depth interviews with twelve mothers who participated in a follow-up program using early intervention for mothers with LBWIs from September 2017 to December 2017. Colaizzi's method was used to analyze the data. Results: The experience of mothers' attachment was investigated on the basis of three categories: 'beginning of changes in parenting methods,' 'forming an intimate mother-child bond,' and 'concerns and expectation about the child's development.' Conclusion: The results indicate that the follow-up program using an early intervention designed to increase mothers' confidence in their parenting skills can promote mother' attachment and the quality of life of families with LBWIs. Keywords: affect, early intervention, infant, low birth weight, qualitative research